Inhibitory control is not lateralized in Parkinson's patients. (28th July 2017) - Mirabella, G.; Fragola, M.; Giannini, G.; Modugno, N.; Lakens, Daniel
Abstract: Parkinson's disease (PD) is often characterized by asymmetrical symptoms, which are more prominent on the side of the body contralateral to the most extensively affected brain hemisphere. Therefore, lateralized PD presents an opportunity to examine the effects of asymmetric subcortical dopamine deficiencies on cognitive functioning. As it has been hypothesized that inhibitory control relies upon a right-lateralized pathway, we tested whether left-dominant PD (LPD) patients suffered from a more severe deficit in this key executive function than right-dominant PD patients (RPD). To this end, via a countermanding task, we assessed both proactive and reactive inhibition in 20 LPD and 20 RPD patients, and in 20 age-matched healthy subjects. As expected, we found that PD patients were significantly more impaired in both forms of inhibitory control than healthy subjects. However, there were no differences either in reactive or proactive inhibition between LPD and RPD patients. All in all, these data support the idea that brain regions affected by PD play a fundamental role in subserving inhibitory function, but do not sustain the hypothesis according to which this executive function is predominantly or solely computed by the brain regions of the right hemisphere. Highlights: Voluntary inhibition is thought to rely upon a right-lateralized network. Inhibition was assessed in left-, right-dominant Parkinson's (PD) patients, and in controls . PD patients were significantly more impaired in both reactive and proactive inhibition than controls. However, no differences were found between left- and right-dominant PD patients. At least in PD patients, inhibitory control relies upon a bilateral network.